Selection for shade-tolerance ferns and horticultural utilization - XU Bing; JIN Shui-hu; DING Bing-yang (浙江大学学报. 农业与生命科学版, 2006)
Ten ferns, which were considered to be used in horticulture, were cultivated under three treatments. Ratio of leaf weight and area, chlorophyll content, ratio of Chla. and Chlb., and rate of photosynthesis were measured respectively. Based on these values, the results showed that: (i) Pteris vittata, Angiopteris fokiensis, and Dryopteris erythrosora were the best shade-tolerance species, and Cibotium barometz, Petris multifida, etc. were secondly ones. (ii) Aimed at horticultural utilization, five species were selected, namely Angiopteris fokiensis, Petris multifida, Coniogramme emeiensis, Plagiogyria dentimarginata, and Asplenium wrightii. Constructive proposals were given as well.